RESERVOIR CHARACTERIZATION AND VOLUMETRIC ESTIMATION OF AIR BENAKAT FORMATION, C FIELD, SOUTH SUMATRA BASIN - Jennifer Sugito, Cheryl
C Field is an oil field located in the South Sumatra Basin. This field is currently considered as a development field within coverage area approximately 5,5 x 3,2 km2. The objective of this study is to characterize the reservoir properties, including determining the facies and depositional environment, determining the petrophysical properties, and estimating the volume of original oil in place of Air Benakat Formation (reservoir ABF1, ABF2, and ABF3). The dataset used in this study includes well data from 11 wells in addition to core, biostratigraphy report, and mud log. Core analysis presents that the target intervals consist of four sandstone lithofacies (Scl, Sba, Sfl, Srx) and one claystone lithofacies (MSl). Based on core, ichnofossil, biostratigraphy, and electrofacies analysis, the depositional environment is Middle Miocene tide-dominated estuarine. The facies associations consist of Tidal Mud Flat, Estuarine Channel, and Intertidal Sand Bar with a NE-SW sedimentation trend. Based on petrophysical calculation, the average results of clay volume are 0,45 for ABF1, 0,12 for ABF2, and 0,34 for ABF3, the average results of effective porosity are 0,14 for ABF1, 0,24 for ABF2, and 0,13 for ABF3, and the average results of effective water saturation are 0,84 for ABF1, 0,66 for ABF2, and 0,63 for ABF3. The volumetric estimation shows the volume of ABF1 as 16,14 MMSTB, ABF2 as 11,36 MMSTB, and ABF3 as 6,61 MMSTB.